Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Matematika Pada Materi Statistika Peserta Didik - Dea Apriliyanti; Griet Helena Laihad; Nurlinda Safitri (STKIP Andi Matappa Pangkep, 2023)
This study aims to determine the effect of the Problem Based Learning model on mathematics learning outcomes in the statistical material of fourth grade students at Kedung Waringin Public Elementary School, Bogor City. Using a quasi-experimental research type with nonequivalent control group design. The population in this study were all fourth grade students at Kedung Waringin Public Elementary School, Bogor City for the 2021/2022 academic year, totaling 60 students as well as being the research sample. Based on data analysis, there is a difference between the average pretest and posttest learning outcomes. The research results obtained were 3.62116 > 2.00172 so that H0 was rejected and Ha was accepted. In addition, the learning outcomes proved that the average N-Gain value in the experimental group was 75 while the average N-Gain value in the control group was 62. So it can be stated that there is an influence of the problem-based learning model on mathematics learning outcomes in class student statistics material IV Kedung Waringin Public Elementary School, Bogor City.